2008
DOI: 10.1063/1.2969081
|View full text |Cite
|
Sign up to set email alerts
|

Changing adsorption mode of FePc on TiO2(110) by surface modification with bipyridine

Abstract: Surface modification of reactive oxide substrates to obtain a less strongly interacting template for dye adsorption may be a way to enhance performance in dye-sensitized solar cells. In this work, we have investigated the electronic and structural properties of 4,4(')-bipyridine (bipy) as modifier adsorbed on the TiO(2)(110) surface. The modified surface is then coated with iron phthalocyanine (FePc) and the properties of this heterostructure are investigated with synchrotron based photoelectron spectroscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 46 publications
2
30
0
1
Order By: Relevance
“…The growth is of island type at room temperature. In agreement with previous studies on Pc/TiO 2 , [13][14][15][16] it is found that charge is transferred away from the molecular HOMO into the substrate. Further comparison between NEXAFS resonance shifts and PES shifts points to a considerable screening difference between molecular center and periphery.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The growth is of island type at room temperature. In agreement with previous studies on Pc/TiO 2 , [13][14][15][16] it is found that charge is transferred away from the molecular HOMO into the substrate. Further comparison between NEXAFS resonance shifts and PES shifts points to a considerable screening difference between molecular center and periphery.…”
Section: Discussionsupporting
confidence: 81%
“…TiO 2 is usually used as the working electrode for such devices. Previously, we have found that Pc molecules (FePc, 13,14 TiOPc, 15 and H 2 Pc (Ref. 16)) suffer from electron depletion when absorbed on TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The 2,2′ Bipy peak is found at 286.4 eV and is much broader while the 4,4′ Bipy spectrum has a clear structure with two resolved peaks (at 286.5 and 285.8 eV), which was explained earlier as due to chemical shifts between C-N and C-C and also the influence of the upright geometry. 25 The additional width in the 2,2′ Bipy spectrum is in line with the split N1s and a more complex adsorption geometry.…”
Section: Resultsmentioning
confidence: 96%
“…Later, experiments showed that preadsorption of a monolayer of 4,4′-bipyridine (4,4′ Bipy) proved to successfully modify the rutile TiO 2 (110) surface, avoiding the oxidation of the first FePc layer on top and leaving FePc in an unperturbed molecular state. 25 In the present work, we extend the previous study based on 4,4′ Bipy and additionally introduce two new pyridine molecules, 4TBP and 2,2′-bipyridine (2,2′ Bipy) coadsorbed with TiOPc. Both pyridines are involved in DSSC applications and are therefore technologically relevant.…”
Section: Introductionmentioning
confidence: 93%
“…Up to date several studies contribute to knowledge on Pc/TiO 2 system in various configurations, however, mostly the (110) face of rutile titania was considered. [6,7] Therefore, with respect to real applications in which titania is quite often used in a powder form, it is imperative to investigate Pc molecules on other stable faces as well, mainly the (011) plane. [8] We report studies on copper phthalocyanine molecules (CuPc) deposited on the (011) surface of rutile titania at coverage below 2 ML.…”
mentioning
confidence: 99%